Предмет: Химия,
автор: Полечка666
Ba(OH)2+Na2SO4---BaSO4+2NaOH Ребят, как составить уравнение?
Ответы
Автор ответа:
0
Ba(OH)2 + Na2SO4 = BaSO4↓ + 2NaOH
Ba(2+) + 2OH(-) + 2Na(+) + SO4(2-) = BaSO4↓ + 2Na(+) + 2OH(-)
Ba(2+) + SO4(2-) = BaSO4↓
Автор ответа:
0
Na2SO4 + Ba(OH)2 = BaSO4↓ + 2NaOH
Полная
форма: 2Na+ + SO42− + Ba2+ + 2OH− = BaSO4↓ + 2Na+ + 2OH−
Краткая
форма: SO42− + Ba2+ = BaSO4↓
Похожие вопросы
Предмет: Қазақ тiлi,
автор: annagalat2006
Предмет: Информатика,
автор: atghdhg
Предмет: Английский язык,
автор: Аноним
Предмет: Алгебра,
автор: Daaaaaasha